2020
DOI: 10.1016/j.jfca.2020.103467
|View full text |Cite
|
Sign up to set email alerts
|

The phenolic compounds, tocopherols, and phytosterols in the edible oil of guava (Psidium guava) seeds obtained by supercritical CO2 extraction

Abstract: This article is made publicly available in the institutional repository of Wageningen University and Research, under the terms of article 25fa of the Dutch Copyright Act, also known as the Amendment Taverne. This has been done with explicit consent by the author.Article 25fa states that the author of a short scientific work funded either wholly or partially by Dutch public funds is entitled to make that work publicly available for no consideration following a reasonable period of time after the work was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…As reported by Kobori and Jorge (2005), the saponification value of guava seed oil as 189.1 which is higher than reported in our study. If the saponification values are lower, either there are fewer ester linkages or the mean molecular weight of fatty acids is lower (Narváez‐Cuenca et al, 2020). Iodine value is the measure of degree of unsaturation in oil sample.…”
Section: Resultsmentioning
confidence: 99%
“…As reported by Kobori and Jorge (2005), the saponification value of guava seed oil as 189.1 which is higher than reported in our study. If the saponification values are lower, either there are fewer ester linkages or the mean molecular weight of fatty acids is lower (Narváez‐Cuenca et al, 2020). Iodine value is the measure of degree of unsaturation in oil sample.…”
Section: Resultsmentioning
confidence: 99%
“…The identified compounds as shown in Figure 1 were assorted into different chemical classes. Identification of the compounds was achieved based on HR-ESIMS data and comparison with literature data as follows: Cis-3-Hexenyl isobutyrate (1) [37], cinnamyl acetate (2) [38], coumaric acid (3) [39], β-sitosterol (4) [39], α-tocopherol (5) [39], linoleic acid (6) [39], palmitic acid (7) [39], stearic acid (8) [39], oleic acid (9) [39], linolenic acid (10) [39], vanillic acid (11) [39], 4-Hydroxybenzaldehyde (12) [39], vanillin (13) [39], syringaldehyde (14) [39], coniferylaldehyde (15) [39], sinapaldehyde (16) [39], abscisic acid (17) [39], cinnamic acid (18) [39], cinnamaldehyde (19) [39], campesterol (20) [39], stigmastanol (21) [39], stigmasterol (22) [39] and quercetin 4 -glucuronide (23) [40]. Guava seed extract provided substantial protection against the ulcerogenic effects of indomethacin in a dose-dependent manner (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Mezni et al found α-and c-tocopherols at the concentrations of 119 mg/kg and 23 mg/kg of oil, respectively, using HPLC analysis [18]. In a recent study, the yield of edible oil was 8.6 ± 1.2 g oil/100 g of guava seeds by supercritical CO 2 extraction, and then the c-tocopherol with a concentration of 82.6 ± 3.7 mg/100 g oil was detected by the GC-MS method [19]. One of the most important products derived from fruit is Hass avocado (Persea americana Mill.)…”
Section: Distribution Of Tocols In Foods: Occurrencementioning
confidence: 99%